Parenteral Nutrition in Interventional Radiology: Consideration and Management of the Patient - Moon, Eunice; Kapoor, Baljendra; Wang, Weiping (Digestive Disease Interventions, 2018)
The approach for patients on parenteral nutrition is typically multidisciplinary. Catheters for parenteral nutrition are primarily placed by interventional radiologists under image guidance. Therefore, adequate knowledge of different catheters, including their indications and complications, as well as management of the complications is exceptionally important for interventional radiologists as well as the referring service. In this review, we discuss different aspects of parenteral nutrition, including infectious complications and the strategy for their prevention and management.
Keywords: parenteral nutrition; catheters; infection